Risk factors for colonization with multidrug-resistant Gram-negative bacteria and Clostridioides difficile in Long Term Care Facilities (LTCFs) residents: the evidence from 27 facilities in a high endemic setting - Azzini, Anna Maria; Be, Giorgia; Naso, Laura; Lambertenghi, Lorenza; Salerno, Nicola Duccio; Coledan, Ilaria; Bazaj, Alda; Mirandola, Massimo; Miotti, Jessica; Mazzaferri, Fulvia; Accordini, Simone; Lo Cascio, Giuliana; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Residency in LTCFs increases the likelihood of colonization with multidrug resistant Gram-negative bacteria (MDR-GNB). We assessed the prevalence and risk factors for enteric colonization by III-generation cephalosporins-resistant and carbapenem-resistant (CR) GNB in a large group of LTCFs in a high endemic setting. We also assessed the prevalence and risk factors for C. difficile colonization. Methods A point prevalence survey with rectal screening (RS) was conducted in 27 LTCFs in north Italy. Epidemiological and clinical variables on the survey day, history of hospitalization and surgery within one year, and antibiotics within three months, were collected. The presence of III-generation cephalosporin resistant and CR GNB was assessed using a selective culture on chromogenic medium and PCR for carbapenemase detection. The presence of C. difficile was assessed using ELISA for GDH and RT-PCR to identify toxigenic strains. Multi-variable analyses were performed using two-level logistic regression models. Results In the study period 1947 RSs were performed. The prevalence of colonization by at least one GNB resistant to III-generation cephalosporin was 51% (E. coli 65%, K. pneumoniae 14% of isolates). The prevalence of colonization by CR GNB was 6%. 6% of all isolates (1150 strains) resulted in a carbapenem-resistant K. pneumoniae, and 3% in a carbapenem-resistant E. coli. KPC was the most frequent carbapenemase (73%) identified by PCR, followed by VIM (23%). The prevalence of colonization by C. difficile was 11.7%. The presence of a medical device (OR 2.67) and previous antibiotic use (OR 1.48) were significantly associated with III-generation cephalosporin resistant GNB colonization. The presence of a medical device (OR 2.67) and previous hospitalization (OR 1.80) were significantly associated with CR GNB. The presence of a medical device (OR 2.30) was significantly associated with C. difficile colonization. Main previously used antibiotic classes were fluoroquinolones (32% of previously treated subjects), III-generation cephalosporins (21%), and penicillins (19%). Conclusion Antimicrobial stewardship in LTCFs is a critical issue, being previous antibiotic treatment a risk factor for colonization by MDR-GNB. The prevalence of colonization by III-generation cephalosporin and CR GNB among LTCF residents also underlines the importance to adhere to hand hygiene indications, infection prevention and control measures, and environmental hygiene protocols, more achievable than rigorous contact precautions in this type of social setting.